ANALYSIS OF SERUM OXIDANT – ANTIOXIDANT STATUS IN PATIENTS WITH IRON DEFICIENCY ANEMIA (IDA) - MUTHULAKSHMI MUTHIAH; RANJIT SIVANANDHAM; KANNAN R; SHWETA KHANDELWAL; SURAPANENI KRISHNA MOHAN (International Journal of Pharma and Bio Sciences, 2013)
Iron deficiency is the most common deficiency worldwide, with negative effects on work capacity and on motor and mental development of infants, children, and adolescents, particularly in developing countries. Free radicals were generated due to the oxidative damage to the red blood cells and the exact pro-oxidant & antioxidant status in iron deficiency anemia was still ambiguous. Hence we have conducted this study not only to analyse but also to gain new insights into the oxidant-antioxidant status in patients diagnosed with iron deficiency anemia. This study was conducted in Saveetha Medical College & Hospital, Saveetha University with twenty patients diagnosed with iron deficiency anemia as study subjects and twenty age & sex matched healthy individuals as controls. Hemoglobin, ferritin, malondialdehyde, glutathione levels and the activity of the glutathione-s-transferase were measured in study subjects and compared to controls. There was a significant increase in malondialdehyde levels confirming the existence of oxidative stress in patients with iron deficiency anemia, compared to controls. The non-enzymatic and enzymatic antioxidants viz. glutathione and glutathione-s-transferase were beneficial in combating with the oxidative stress and this was evident with the decreased levels of the same in these patients compared to controls. The results of our study emphasize the use of antioxidants as a secondary therapy to reduce the oxidative damage in patients with iron deficiency anemia.